Role Of Rakta Dhatu In Human Body - Kour, Maninder; Rana, Sanjeet Singh (International Research Journal of Ayurveda & Yoga, 2021)
Rakta Dhatu is the second dhatu among the seven dhatu. Growth and nourishment of the body takes place by dhatus. Dhatus are functional apparatus of the dosha. Dhatu gives ashraya, which does dharana and poshana(support and nourishes the body). Rakta dhatu is produced from the prasad bhaga of rasa dhatu with the help of Bhutagni and Rasa dhatwagni. Teja and jala mahabhuta is predominant in rakta dhatu. Sathans(seat) of rakta dhatu is raktavahasrotas. Sushruta mentioned that Rakta Dhatu is base of living body; it maintains life, so one should take proper care of Rakta Dhatu by proper diet that gives nourishment to Rakta. Acharya charak has described 8 anjali praman of rakta dhatu. organ of this srotas are liver and spleen.